2017
DOI: 10.3892/mco.2017.1130
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of metformin for advanced-stage endometrial cancer: A case report

Abstract: Abstract. The paradigm of obesity, diabetes mellitus and insulin resistance possibly plays a critical role in the pathogenesis of endometrial cancer (EC). Impaired glucose tolerance and insulin resistance may play a direct or facilitating role in the neoplastic transformation of the endometrium, whereas antidiabetic therapy, particularly with metformin, has been suggested to inhibit EC progression. We herein present the case of a patient with EC who recei�ed metformin mono-EC who recei�ed metformin monowho rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Previous findings have shown that obesity is the primary risk factor for endometrial cancer, and weight 13.5 and 22.5 kg higher than the ideal value can increase the risk of endometrial cancer by 3- and 10-fold, respectively ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings have shown that obesity is the primary risk factor for endometrial cancer, and weight 13.5 and 22.5 kg higher than the ideal value can increase the risk of endometrial cancer by 3- and 10-fold, respectively ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other important signaling pathways were also identified, such as PI3K/AKT/mTOR and MAPK/ERK [46,47]. Several clinical trials and case reports of metformin treatment as a single agent or combination with other treatments have been established; for example, a phase II/III trial will add metformin or placebo to paclitaxel/carboplatin as the first-line therapy for advanced EC (NCT02065687) [45,48]. Some studies have produced promising data.…”
Section: Mitochondrial Functionmentioning
confidence: 99%